Aves de sotobosque en época de vaciante del bosque de terraza inundable por agua negra del sector Yarana en la Reserva Nacional Allpahuayo Mishana - río Nanay, Loreto - Jesús Schermully de Rojas, Nancy Carmina (2022)
From august to october 2020, we have studied the composition and abundance of understory birds in non-floodable season from flooded forest black water forest in Yarana zone – Nanay river, by capture with nets. Birds were made up of 10 orders in which stood out Passeriformes, Apodiformes, Columbiformes, Piciformes, Galbuliformes and Cuculiformes orders whom reported the majority numbers of species. The Passeriformes reported 11 families and 41 species, Apodiformes with 1 family and 6 species, Columbiformes with 1 family and 5 species, while others orders reported one family and one specie like Tinamiformes, Anseriformes, Coraciiformes and Trogoniformes, with a richness of 65 species. The over-all capture effort was 0.057 ind/hours-net, and at the species level was low (les of 1 ind/hours-net. The species with more index for effort of capture were Glyphorhynchus spirurus (0.003 ind/hour-net), Thraupis palmarum and T. episcopus (with 0.002 ind/hour-net respectively). In conclusion, the composition and abundance of understory birds in non-floodable season from flooded forest black water forest in Yarana zone – Nanay river was dominated for Passeriformes order with a medium richness.